Cystitis – Scope of Homeopathy (Homoeopathy for All, 2021)
In health, the upper urinary tract it sterile but the lower urinary tract there are bacteria which thrive in lower urinary tract. The urinary tract can become infected with various bacteria but the most common is E. coli derived from the gastrointestinal tract. The most common presenting problem is cystitis with urethritis (generally referred to as urinary tract infection).1 1Urinary tract infection (UTI) is the term used to describe acute urethritis and cystitis caused by a microorganism. It is a common disorder, accounting for 1–3% of consultations in general medical practice. The prevalence of UTI in women is about 3% at the age of 20, increasing by about 1% in each subsequent decade. In males, UTI is uncommon, except in the first year of life and in men over 60, when it may complicate bladder outflow obstruction.1
Keywords: Clinical features; microorganism